Unfriend or ignore tweets?: A time series analysis on Japanese Twitter users suffering from information overload. (November 2016) - Sasaki, Yuichi; Kawai, Daisuke; Kitamura, Satoshi
Abstract: In recent years, with increased opportunities to post content on social media, a number of users are experiencing information overload in relation to social media use. This study addresses how Japanese Twitter users suffering from information overload cope with their stress, focusing on two actions: (1) The "unfriending" activities and (2) The changes in tweet processing methods. Objective data, such as numbers of friends, were collected through Twitter's open Application Programming Interfaces (APIs), and subjective data, such as perceived information overload and tweet processing methods, were collected through a web-based survey as a panel dataset ( n  = 778). The results demonstrated that although users experience information overload, they continue to increase their number of friends, and that the users who experience information overload modify their usage habits to avoid seeing all received tweets. In short, users do not choose a strategy to reduce the absolute number of received tweets, but only a strategy that involves changing the processing method of the received tweets. Highlights: We analyzed the coping strategies that information-overloaded Japanese Twitter users employ. In Twitter, users can control the amount of information on their own initiative. More than one third of users do not view all received tweets. In spite of information overload, users continue to increase the number of friends. The more the users feel information overloaded, the more they avoid viewing all tweets.